PERANCANGAN SISTEM PENDAFTARAN CALON KEPALA DESA DI DINAS PEMBERDAYAAN MASYARAKAT DAN DESA (DPMD) KABUPATEN BANYUWANGI - Rendi Wijayakusuma; Farihin Lazim (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
The registration process for village head candidates at the Department of Community Empowerment and Village (DPMD) of Banyuwangi Regency has so far been carried out manually, which can lead to various issues such as delays in document submission, data entry errors, and low service efficiency. This study aims to design a web-based registration system that facilitates the registration process online, making it more effective and transparent. The methodology used in this system design includes data collection through observation and interviews, system requirements analysis, system modeling using Unified Modeling Language (UML), and user interface (UI) design. The system is designed for two main user types: administrators and applicants. Administrators are responsible for verifying and managing applicant data, while users (village head candidates) can register, fill out forms, and upload documents online. The result of this design is a prototype of an information system for village head candidate registration, which includes features such as login, registration, account management, document upload, user dashboard, and activity logs. The implementation of this system is expected to make the registration process faster, more accurate, and to support transparency and accountability in the village head election process.